GUABIROBEIRA (Campomanesia xanthocarpa BERG.)VEGETATIVE PROPAGATION IN VITRO AND BY CUTTING - BRUNNER SCUTTI, Marcia (Scientia Agraria, 2000)
The guabirobeira (Canvpomanesia xanthocarpa Berg.) is a native woody fruitful Myrtacea of the South region of Brazil whose commercial exploration can be fomented by studies about its vegetative propagation. Several techniques of vegetative propagation were used with the objective of studying the behavior of the species. The work is divided in two phases: cutting and micropropagation. For the semi-woody cutting 2 substratum types were tested (100% Plantmax® 2/3 Plantamax® + 1/3 sand) and 7 treatments (water; ethanol 50%; ethanol 20%; ethanol 40%; IBA 500 mg.L-1; IBA 1.000 mgL-1; IBA 2.000 mg.L-1). For herbaceous cutting 6 treatments were tested (control, water; ethanol 50%; IBA, 1.000 mg.L-1; IBA 5.000 mg.L-1; IBA 10.000 mg.L1) and 2 times of immersion (30 s and 2 hs). there was no formation of roots in none of the experiments. In the micropropagation, the explants source were plants in green house and adult plants from, the field. In all the experiments the desinfesting was based on ethanol and commercial NaOCI and the culture medium was the MS. The experiments with field or green house microcuttings didnt pass of desinfesting plisse, due to the bacterial endogenous contamination. The microcuttings of aseptic plantlets used explants of in vitro germinated seeds from mature fruits or fruits beginning the maturation. The desinfestation was accomplished on fruits or on seeds already separated from the puIp and both forms were efficient. The multiplication test showed that the medium without growth regulators presented longer budding, while the medium with 0,5 mg.L-1 of BAP presented larger budding number by cutting. There was root formation in the medium without growth regulators. In the meristems culture, apical and axillary meristems were used. The results demonstrated to be possible the elimination of the bacterial contamination, but there were no development and multiplication of the meristems. The somatic embryogenesis was induced on developed zigotic embryos, removed tom fruits in the initial phase of maturation. Tests were accomplished with several combinations of growth regulators (2,4-D, ANA IRA, BAP and 21-P) in several concentrations, seeking optimizing the phases of the embryogenesis, from induction to the conversion. In the induction phase the formation of somatic embryos occured in flue medium with 0,5 to 1 mg.L-1 2,4-D. The following phases showed that is possible to decrease or retreat the growth regulator, what stimulates the repetitive cycle and allows the development and conversion of the somatic embryos. The formation of somatic embryos in an indirect and direct way was observed. There was conversion of somatic embryos in pIantlets and several passed to the climate adaptation, phase in green house.